Exploring the relationship between self-management and blood glucose level in patient with type 2 diabetes mellitus - Sari, Dwi Yustika; Ariyanti, Anita Dwi; Masroni, Masroni (The Journal of Palembang Nursing Studies, 2023)
Background: Diabetes mellitus (DM) is a condition characterized by high blood sugar levels resulting from unstable blood sugar levels in diabetics. DM can not only be treated with pharmacological therapy but also requires non-pharmacological therapy, one of which is self-management. Objective: to determine the relationship between the level of self-management and blood glucose in type 2 diabetes mellitus. Methods: This research employed a cross-sectional design with 35 respondents selected through an accidental sampling technique. Data collection involved using the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire and a Glucometer. The data were then analyzed using the Spearman Rank Test.  Results: The data analysis revealed that 62.9% of patients with Type 2 DM experienced self-management in the medium category, and 88.6% had blood sugar levels in the high category. Based on the analysis results, a p-value of 0.180 was obtained, indicating that there is no relationship between self-management and blood glucose levels in patients with type 2 diabetes mellitus. The correlation coefficient of -0.232 indicated a low correlation strength, and as the correlation coefficient is negative, the relationship between the two variables is not in the same direction. Conclusions: It is evident that need more investigation of self-management practices to achieve stable or normal blood sugar levels. Improving self-management is crucial as it can help prevent complications associated with diabetes mellitus.